2016
DOI: 10.1038/srep26020
|View full text |Cite
|
Sign up to set email alerts
|

The N-end rule pathway regulates pathogen responses in plants

Abstract: To efficiently counteract pathogens, plants rely on a complex set of immune responses that are tightly regulated to allow the timely activation, appropriate duration and adequate amplitude of defense programs. The coordination of the plant immune response is known to require the activity of the ubiquitin/proteasome system, which controls the stability of proteins in eukaryotes. Here, we demonstrate that the N-end rule pathway, a subset of the ubiquitin/proteasome system, regulates the defense against a wide ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 67 publications
2
60
2
Order By: Relevance
“…In this paper, we report the effects of loss of PRT1 function on the immune system. A previous report showed that the prt1 mutant was more susceptible to the hemi‐biotroph bacterium Pseudomonas syringae pv tomato in short‐day plants (de Marchi et al, ); however, using an assembly of different approaches, we show that removal of the activity of the PRT1 E3 ligase enhances resistance of arabidopsis to this pathogen, and that this is associated with constitutive alteration of the proteome including the enhanced accumulation of many pathogenesis‐associated proteins. In addition, we show an altered metabolome profile in the mutant including SA, camalexin, and, together with prt6 mutant, Pip.…”
Section: Introductioncontrasting
confidence: 59%
“…In this paper, we report the effects of loss of PRT1 function on the immune system. A previous report showed that the prt1 mutant was more susceptible to the hemi‐biotroph bacterium Pseudomonas syringae pv tomato in short‐day plants (de Marchi et al, ); however, using an assembly of different approaches, we show that removal of the activity of the PRT1 E3 ligase enhances resistance of arabidopsis to this pathogen, and that this is associated with constitutive alteration of the proteome including the enhanced accumulation of many pathogenesis‐associated proteins. In addition, we show an altered metabolome profile in the mutant including SA, camalexin, and, together with prt6 mutant, Pip.…”
Section: Introductioncontrasting
confidence: 59%
“…Another upregulated protein, GSTF7 was hypothesized to play a role in camalexin synthesis based on its induction in the constitutively active MKK9 mutant (Su et al ., ). Our analysis of previously published transcriptome data (de Marchi et al ., ) comparing gene expression in ate1 ate2 with WT, and comparing gene expression during Pst infection in Col‐0 and ate1 ate2 also showed increased expression of RNAs encoding camalexin synthesis genes (Tables S3, S4). Analysis of transcript expression indicated greater accumulation for most genes of camalexin synthesis in mature uninfected leaves of ntaq1 and prt6 compared to WT (Figs , S7), including PAD3 (CYP71B15), that catalyzes the final two steps of camalexin synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…These results are opposite to those obtained by de Marchi et al . (), who found enhanced sensitivity to Pst DC3000 of N‐end rule mutants prt6 and ate1 ate2 (which removes ATE Nt‐arginylation activity, Fig. a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations